Kondisi Demokrasi Indonesia Antara Harapan dan Kekhawatiran Pasca Pemilu 2024 - M Salman Alfariji (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Indonesia's democracy has been at the center of intense debate in recent years, with many parties criticizing its increasingly fragile and threatened state. This article aims to analyze why Indonesian democracy is considered destroyed by some parties. First, the analysis begins by examining the decline in the quality of democracy which is reflected in the classification of Indonesian democracy in the implementation of its government. Data showing a decline in civil liberties, suppression of freedom of expression, and abuse of power by those in power that threaten democratic principles. Internal and external factors that contributed to the collapse of democracy in Indonesia. Among the internal factors are abuse of power, corruption, and the inability of institutions to provide adequate protection for citizens' rights. Meanwhile, external factors include geopolitical pressures and the influence of globalization on domestic politics. Such as political polarization that triggers conflict, lack of active participation from civil society, and lack of consolidation of democratic institutions.